Smart Dustbin Penyortiran Sampah Basah Dan Kering Berbasis IOT Menggunakan Aplikasi Blynk - Dari, Natasya Wulan; Suharjo, Imam (JATISI, 2024)
Smart dustbin is an application of IoT in the field of hygiene to increase efficiency in sorting wet and dry waste automatically, using gas sensors and buzzer speakers as a warning if smoke is detected which indicates a fire. Serial communication between Arduino Uno and NodeMCU esp8266 connects the system to a Wifi connection where data will then be sent to the blynk application to control the height level of waste in the waste container. Based on the trials that have been carried out, the results of the wet and dry waste sorting trials reached 90%, for the gas sensor and buzzer smoke detector trials went well with 100% results. controlling the trash height level from the blynk application, the percentage of trash height level goes up and down.